1998
DOI: 10.1016/s0275-5408(97)00068-9
|View full text |Cite
|
Sign up to set email alerts
|

The underachieving child

Abstract: Visual factors in specific learning difficulties (SpLD) are reviewed. People with SpLD fail to achieve at a level that is commensurate with their intelligence. The commonest SpLD is dyslexia, which usually results from phonological processing/decoding deficits. Additionally, there are several optometric correlates of SpLD which may, in some cases, contribute to the learning difficulty. These correlates include binocular instability and a low amplitude of accommodation. Some people with reading difficulties and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 62 publications
0
14
0
Order By: Relevance
“…Our mean MAA values did not differ statistically among the school grades examined, neither for the poor readers or the control children, despite the steady reduction with age observed by Jimenez et al [18] (Table 2). Significant correlation between reading problems and a low amplitude of accommodation have been reported [4,5]. Thus, Evans et al [24] detected a significantly lower amplitude of accommodation in a group of dyslexic children (n = 39) than in their control group (n = 43).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Our mean MAA values did not differ statistically among the school grades examined, neither for the poor readers or the control children, despite the steady reduction with age observed by Jimenez et al [18] (Table 2). Significant correlation between reading problems and a low amplitude of accommodation have been reported [4,5]. Thus, Evans et al [24] detected a significantly lower amplitude of accommodation in a group of dyslexic children (n = 39) than in their control group (n = 43).…”
Section: Discussionmentioning
confidence: 91%
“…Even if a child shows subjective symptoms when reading, this is often not the primary function tested in an examination. Significant correlation between reading problems and low amplitude of accommodation [4,5] and accommodative facility have been reported [6][7][8]. On the other hand, several authors have observed no statistical relationship between accommodative function and academic performance [9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Visual stress questionnaires are problematic because many symptoms can be attributed to binocular vision and accommodative anomalies as well as decoding problems. Given that increased rates of visual and oculomotor difficulties have been reported in individuals with dyslexia (Evans, 1998; 2001; Evans et al., 1999), the higher scores for the dyslexic group on the questionnaire may not reflect susceptibility to visual stress, but rather, the presence of other visual anomalies. This is problematic since overlays are frequently distributed solely on the basis of symptom questionnaires or subjective beneficial reports of coloured overlays or lenses without a formal assessment of optometric function.…”
Section: Discussionmentioning
confidence: 99%
“…Meta-analysis has also shown signi®cant associations between reading performance and hyperopia, exophoria at near, vertical phoria, anisometropia and aniseikonia (Simons and Grisham, 1987). Signi®cant correlation between reading problems and poor fusional vergence reserves, convergence insuciency and ®xation disparity (Simons and Grisham, 1987), binocular instability and low amplitude of accommodation (Evans, 1998;Evans et al, 1999), and accommodative facility (Hennessey et al, 1984) have also been reported. The continuing association of subtle impairments in visual function and reading disability in the scienti®c literature is no longer controversial (Fowler, 1991).…”
Section: Introductionmentioning
confidence: 99%